P11 Assessment of malignancy in patients with idiopathic pulmonary embolus: an audit. (2nd December 2011) - Som, R
Abstract : Background: There are 65 000 cases of pulmonary embolus (PE) in hospital per year in England and Wales. There is a significant association between idiopathic venous thrombosis and cancer and an increase in risk of diagnosis of cancer within a year of idiopathic venous thrombosis. The British Thoracic Society (BTS) guidelines suggests that all patients who do not have a major risk factor for PE should receive "a combination of careful clinical assessment, routine blood tests and chest radiography" and only when these indicate possibility of malignancy, should further imaging or invasive investigations for malignancy be considered. Our aim was to evaluate these guidelines in a large teaching hospital in England. Method: A retrospective patient-chart review of all patients admitted with pulmonary embolus over 12 months was performed. A patient was excluded if they had a clear major risk factor for developing PE for example, recent pelvic surgery, known malignancy etc. If a patient had no clear risk factor, the documentation during the admission was reviewed to see whether clinicians were complying with BTS guidelines and assessing for malignancy appropriately. A pro-forma was designed to check this, with 1 point being given for every aspect of history/investigation performed in regards to assessing for cancer for example, 1 point awarded if the patient was asked about recent change in bowel habit; 1 point if the patient's serum calcium was checked. An overall score was given for each clinical assessment for malignancy for each patient (out of 14 for men; out of 15 for women). Results: 202 patients with confirmed PE were admitted over 12 months. 39 patients were included in the study. In summary, compliance with BTS guidelines calling for thorough clinical assessment was poor in a number of parameters—patients were not asked if they were suffering from systemic symptoms of malignancy, or assessed for symptoms and signs of common malignancies associated with PE. Conversely, a number of patients were inappropriately referred for further investigation—particularly imaging—for possible malignancy without a documented history or examination pertaining to a specific malignancy. Conclusion: Compliance with the guidelines from the BTS is poor. Adequate histories and examinations for malignancy are not being performed. This suggests that either the guidelines or the clinical practice needs re-evaluation.